Implementation of Brainstorming Method to Improve Social Studies Learning Achievement of Grade VIII Junior High School Students - Rohmatul Hidayati Maulidiyah Lidiyah; Jani Jani (JURNAL PENDIDIKAN IPS, 2023)
This research is motivated by the observation data that the researchers did that social studies learning is still low in achievement because it is not appropriate to choose the method in conveying the material. Learning using the brainstorming method, which was carried out at SMP "Empat Lima" Karanggeneng Lamongan, was assessed as being able to improve learning achievement. The goal is to know the steps, supporting factors, accelerating factors, and the impact of applying the brainstorming method. The method used is the descriptive qualitative method. Data collection techniques are using interviews, documentation and observation. The benefit of research is that students can improve their achievement. Students can convey ideas and new solutions according to the material, which can increase self-confidence. The research was conducted at SMP "Empat Lima" Karanggeneng Lamongan in class VIII with a total of 17 students. The brainstorming method is a method in which students are trained to be able to provide opinions and solutions, and students are given breadth without any criticism or objection. This brainstorming method is suitable for use in social studies lessons, especially at the junior high school level. The brainstorming method can improve learning achievement because students can obtain new information and knowledge from seeking references so that students can think creatively and innovatively, and it can also increase students' self-confidence. The steps of the brainstorming method properly and correctly can increase student achievement. Learning the brainstorming method also has supporting factors, boosters and a positive impact on students.